Stock Returns and Investor Hype - Mulder,Oscar Leonard (2025)
Investors are constantly seeking information that can provide a competitive advantage in the market. Using online platforms along with traditional media sources supply a constant source of information available to investors. Among the available information, Google Trends scores provide insights into investor attention and sentiment. To understand whether there is a relationship between Google Trends and investor behaviour, reflective of the returns, a quantitative event study was conducted. The event study (following MacKinlay’s guide from 1997) focuses on moments of increased investor attention for a stock and/or security. The findings of this thesis indicate a significant relationship between abnormal returns and events of increased hype. These findings led to a second research question regarding the nature of said relationship. Further analysis of trade volume deviation during events shows that hype can work as a proxy for increased trade volume, resulting in negative abnormal returns. This thesis concludes that Google Trend scores can work as a viable variable in predicting stock returns during extremities.
Keywords: Google Trends; Event Study; Abnormal Returns